(untitled) (International Journal of Food and Nutritional Sciences, 2023)
this abstract emphasizes the importance of addressing the nutritional challenges faced by adolescent girls in rural areas. These girls play a crucial role in community well-being, but often struggle with poor nutrition, impacting their health and development. To achieve sustainable development goals, the abstract suggests the need for targeted nutrition education programs designed specifically for these girls.